USE OF DIFFERENT DOSES OF OVAPRIM TO INDUCED LELAN (Osteochilus pleurotaenia Blkr) - Tri Suryati Bakkara; Netti Aryani; Adelina ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted from May 23 to December 6 2015. The aim of this research was to determine the effect of ovaprim doses on spawning success of lelan fish (Osteochilus pleurotaenia Blkr). The method used in this research was an experimental method with Completely Randomized Design (CRD) with one factor, four treatments and three replications. The treatment used in this research was an injection of ovaprim with different doses i.e : P0 (0,2 mL NaCl physiology 0,9 %/kg of body weight), P1 (0,5 mL/kg of body weight), P2 (0,6 mL/kg of body weight) and P3 (0,7 mL/kg of body weight). The results showed that ovaprim dose of 0,6 mL/kg of body weight was the bestin turn of latencytime (6.08 hours), total eggs stripping (30.024 eggs/g gonads), egg diameter (0,827 mm), egg maturity (84,443%), Ovi Somatic Index (20,15%), fertility rate (20,01%), hatching rate (19,43 %), and survival rate (29,93 %). Keywords : Ovaprim, Spawning, Lelan (Osteochilus pleurotaenia Blkr).